2003
DOI: 10.1152/jn.00993.2002
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Regulation of REM Sleep in Reticularis Pontis Oralis and Caudalis in Rats

Abstract: The nucleus reticularis pontis oralis (RPO) and nucleus reticularis pontis caudalis (RPC) are implicated in the generation of rapid eye movement sleep (REM). Work in cats has indicated that GABA in RPO plays a role in the regulation of REM. We assessed REM after local microinjections into RPO and RPC of the gamma-aminobutyric acid-A (GABA(A)) agonist, muscimol (MUS), and the GABA(A) antagonist, bicuculline (BIC). Rats (90-day-old male Sprague-Dawley) were implanted with electrodes for recording electroencephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
89
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 20 publications
12
89
0
1
Order By: Relevance
“…The greater effects of CRH and AST on wakefulness and sleep in BALB/cJ mice compared to C57BL/6J mice are consistent with findings that BALB/cJ mice are more reactive in behavioral tests of anxiety (Belzung and Griebel, 2001;Tang et al, 2002b) and also show greater alterations in sleep in response to a number of stressors (Wurbel et al, 1998;Sanford et al, 2003a;2003b;2003d). Thus, strain differences in the effects of CRH and AST may be linked to underlying differences in the CRH system that may also be involved in the relative responsiveness to stressors in C57BL/6J and BALB/cJ mice.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The greater effects of CRH and AST on wakefulness and sleep in BALB/cJ mice compared to C57BL/6J mice are consistent with findings that BALB/cJ mice are more reactive in behavioral tests of anxiety (Belzung and Griebel, 2001;Tang et al, 2002b) and also show greater alterations in sleep in response to a number of stressors (Wurbel et al, 1998;Sanford et al, 2003a;2003b;2003d). Thus, strain differences in the effects of CRH and AST may be linked to underlying differences in the CRH system that may also be involved in the relative responsiveness to stressors in C57BL/6J and BALB/cJ mice.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, exposure to an open field induced greater initial reductions with less subsequent increases in REM in BALB/cJ mice whereas C57BL/6J mice exhibited relatively less initial reductions but greater subsequent increases (Tang et al, 2004;. Based on these results, we suggested that the putative trait anxiety in BALB/ cJ mice might play a critical role in the relatively greater effects on REM induced by stressors (Liu et al, 2003;Sanford et al, 2003a;2003b;2003d;Liu et al, 2004;.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…GABAergic and cholinergic transmission interact in the pontine reticular formation to regulate sleep and wakefulness (Vazquez and Baghdoyan, 2004). Microinjection data from cat (Xi et al, 1999), rat (Sanford et al, 2003), and mouse (Chang et al, 2005, Chang et al, 2006 concur in showing that GABAergic transmission in the pontine reticular formation promotes wakefulness. Therefore, the present study was designed to test the hypothesis that μ-opioid receptors in the oral portion of rat pontine reticular formation (PnO) modulate PnO GABA levels.…”
mentioning
confidence: 99%